1997
DOI: 10.1016/s0014-5793(96)01443-3
|View full text |Cite
|
Sign up to set email alerts
|

A fragment of the major histocompatibility complex class II – associated p41 invariant chain inhibits cruzipain, the major cysteine proteinase from Trypanosoma cruzi

Abstract: A peptide fragment derived from the p41 form of the invariant chain (Ii) associated with the major histocompatibility complex (MHC) class II molecule has been shown to inhibit the mammalian lysosomal cysteine proteinase, cathepsin L, and to be a novel cysteine proteinase inhibitor, distinct from cystatins. Here we report that this same fragment also binds to and inhibits cruzipain, the cathepsin L-like enzyme from the protozoan parasite Trypanosoma cruzi. The binding of the Ii fragment to cruzipain is fast (k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The wedge-shaped and three-loop arrangement of this fragment bound to the active-site cleft of cathepsin L is reminiscent of the binding of cystatins [74], thus demonstrating the first example of convergent evolution observed in cysteine protease inhibitors, similar to chagasin [262]. Recently, it has been shown that the p41 fragment inhibits human cathepsins V, K, S and F and mouse cathepsin L with K i values in the nM range [263] in addition to human cathepsin L [227] and cruzipain [226]. These findings suggest that the regulation of the proteolytic activity of most of the cysteine cathepsins by the p41 fragment has an important and wideranging control mechanism of antigen presentation [263].…”
Section: Mechanism Of Inhibition Of Cysteine Cathepsinsmentioning
confidence: 84%
See 1 more Smart Citation
“…The wedge-shaped and three-loop arrangement of this fragment bound to the active-site cleft of cathepsin L is reminiscent of the binding of cystatins [74], thus demonstrating the first example of convergent evolution observed in cysteine protease inhibitors, similar to chagasin [262]. Recently, it has been shown that the p41 fragment inhibits human cathepsins V, K, S and F and mouse cathepsin L with K i values in the nM range [263] in addition to human cathepsin L [227] and cruzipain [226]. These findings suggest that the regulation of the proteolytic activity of most of the cysteine cathepsins by the p41 fragment has an important and wideranging control mechanism of antigen presentation [263].…”
Section: Mechanism Of Inhibition Of Cysteine Cathepsinsmentioning
confidence: 84%
“…The discovery that a fragment of the p41 invariant chain (p41Ii) associated with MHC class-II molecules inhibits cathepsin L [194,226,227] suggested the appearance of a new family of protein inhibitors of cysteine cathepsins. This finding was confirmed by the discovery of a new protein, equistatin, isolated from the sea anemone Actinia equina, strongly inhibiting cathepsin L and papain [228] and human cathepsin D [229].…”
Section: Thyropinsmentioning
confidence: 99%
“…Two inhibitors belonging to the recently discovered family of thyropins [88] were shown to be strong inhibitors of cruzipain, with k ass values of 2.4 x 10 7 M -1 s -1 for a fragment of the MHC class II-associated p41 invariable chain [89] and of 6.7 x 10 6 M -1 s -1 for equistatin, from the sea anemone Actinia equina [90].…”
Section: Catalytic Properties: Specificity For Substrates and Inhibitorsmentioning
confidence: 99%
“…to parasites such as Leishmania or Trypanosoma cruzi . These organisms require cysteine proteases for survival and invasion [25].…”
Section: Discussionmentioning
confidence: 99%